1995
DOI: 10.1111/j.1365-3040.1995.tb00361.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic performance, chloroplast pigments and mineral content of Norway spruce (Picea abies (L.) Karst.) exposed to SO2 and O3 in an open‐air fumigation experiment

Abstract: Photosynthetic performance, mineral content and chloroplast pigments were investigated in August‐September 1988 and 1989 in Norway spruce trees (Picea abies (L.) Karst.) exposed to SO2, and O3 in an open‐air fumigation facility at Liphook, England. The data do not suggest a treatment effect on the mineral content of the needles in terms of nutrient leaching from the foliage. In addition, there were no direct SO2 and/or O3 effects on the content and/or composition of the chloroplast pigments. However, the long‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 60 publications
0
6
0
1
Order By: Relevance
“…An increase in CO 2 concentration enhances photosynthesis and can cause a reduction in g s . However, exposure to pollutants such as O 3 and SO 2 also induces stomatal closure, but in contrast is often accompanied by a concomitant decrease in net photosynthesis (A N ) (Matyssek et al 1997;Linzon 1972;Ziegler 1972;Parry and Gutteridge 1984;Martin et al 1988;Wedler et al 1995). Exposure to NOx sometimes leads to an increase in both A N and g s (Gessler et al 2000;.…”
Section: General Effects Of Changes In the Atmosphere On Stable C O A...mentioning
confidence: 99%
“…An increase in CO 2 concentration enhances photosynthesis and can cause a reduction in g s . However, exposure to pollutants such as O 3 and SO 2 also induces stomatal closure, but in contrast is often accompanied by a concomitant decrease in net photosynthesis (A N ) (Matyssek et al 1997;Linzon 1972;Ziegler 1972;Parry and Gutteridge 1984;Martin et al 1988;Wedler et al 1995). Exposure to NOx sometimes leads to an increase in both A N and g s (Gessler et al 2000;.…”
Section: General Effects Of Changes In the Atmosphere On Stable C O A...mentioning
confidence: 99%
“…The effect of sulphur gas emissions on photosynthesis has been reported for Picea abis (L.) Karst. by Wedler et al (1995), and for other species by Legge et al (1978). Winner et al (1985) have shown that SO 2 influences the CO 2 uptake of plants by changing the stomatal adjustment and/or by direct impact on the chloroplasts, and hence on the physiology of photosynthesis.…”
Section: Resultsmentioning
confidence: 97%
“…The content of photosynthetic pigment in leaves, as a non-stomatal factor, was an important factor affecting the assimilation rate affirmatively. As many researchers have previously pointed out, reduction in the concentration of photosynthetic pigment is an indicator of leaf damage induced by atmospheric pollution (Gonzalez et al 2003;Wedler et al 1995;Dirral 1989), implying the damage of membrane integrity (Gonzalez et al 2003). From this point, decreases in net photosynthesis rate for P. orientalis and F. chinensis in the polluted area might be partly attributed to noticeably lower contents of Chl a, Chl b and carotenoid at RS ( Figure 6).…”
Section: Responses Of Gas Exchangementioning
confidence: 88%